2020
DOI: 10.3389/fpsyg.2020.02045
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Entrepreneurship Education by Linear Regression and Psychological Factor Analysis

Abstract: To study the improvement of the entrepreneurial performance of start-ups and achieve an organic combination of entrepreneurship education and entrepreneurial performance, the entrepreneurial group of college students was taken as the springboard to discuss the entrepreneurial performance of start-ups initiated by college students. First, through questionnaire design and scale selection, the results of the questionnaire survey and the reliability and validity of the scale tool were tested. Second, the variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Moreover, the theory suggests that the higher the absolute value of β becomes, the stronger the effect. This is consistent with research on Chinese entrepreneurial education by Mu et al (2020), who stated that a quantitative analysis frequently uses linear regression analysis to accomplish the data analysis in which β can be used to characterise the correlation between the variables.…”
Section: Mean Sd Element Weights and R2 Valuessupporting
confidence: 86%
“…Moreover, the theory suggests that the higher the absolute value of β becomes, the stronger the effect. This is consistent with research on Chinese entrepreneurial education by Mu et al (2020), who stated that a quantitative analysis frequently uses linear regression analysis to accomplish the data analysis in which β can be used to characterise the correlation between the variables.…”
Section: Mean Sd Element Weights and R2 Valuessupporting
confidence: 86%
“…The objective of college social and political education (SPE) is to improve the social, political, and moral qualities of teachers and students through certain social concepts, political views, and ethical norms education ( Du et al, 2020 ; Li et al, 2020 ; Wu A. et al, 2020 ). College SPE has a particular practical significance by providing solid support for the critical force of China’s economic construction, college entrepreneurs, IEE, and sports ( Mu et al, 2020 ; Philpot et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that nearly half of the students think that they are better in will quality, and less than half of the students think that their will quality needs to be strengthened. Mu et al ( 2020 ) showed that in the evaluation of their temper and character, the number of students who choose good, general, very good, poor, and very poor is 63, 52, 35, 16, and 13, respectively. Raza et al ( 2021 ) indicated that the vast majority of college students think that they have an ordinary or better temper and character, and only a few of the students think that their temper and character are very bad.…”
Section: Research Results and Analysismentioning
confidence: 99%